Analysis and Necessity of Developing the Strategy and Strategic Planning of Organizations in the International Coronavirus Crisis - Muhammad Moghbeli (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today's world is the era of information and communication technology and many experts believe that the outbreak of Coronavirus in this era has significantly affected various areas of human life, including managerial, social, political, economic, educational and other issues. This virus has crossed different boundaries in a short period of time. COVID-19 has disgraced and oppressed the organizations which had no human-like perspective on the retention of their organization. On the contrary, this virus created a new opportunity for organizations in the new managerial discipline to aggravate themselves during the outbreak, transition and post-heat of the outbreak of this crisis and also gain some benefits through management. The present study aimed to analyze the necessity of developing the strategy and strategic planning of organizations in the international coronavirus crisis. The difficulty of managing this crisis, especially in the specific conditions of Iran, the unknown nature of this disease, and the lack of sufficient experience provided the context for creativity and various innovations. Such valuable experiences will provide valuable reserves to the health care system in Iran and the world if being managed and turned into explicit knowledge. In addition, neglecting such an issue will lead to the loss of this huge capital.